Nanosized Mn-Ni oxide thin films via anodic electrodeposition: a study of the correlations between morphology, structure and capacitive behaviour. (10th July 2016) - Tahmasebi, Mohammad H.; Vicenzo, Antonello; Hashempour, Mazdak; Bestetti, Massimiliano; Golozar, Mohammad A.; Raeissi, Keyvan
Abstract: The present study addresses the synthesis of manganese-nickel oxide thin films via potentiodynamic anodic electrodeposition as supercapacitor electrodes. We study in particular the effect of the deposition scan rate and of the Ni(II) to Mn(II) molar ratio in the deposition bath on the capacitive behaviour of mixed oxide electrodes. The increase of the nickel content in oxide thin films of composition Nix Mn1-x Oy (with x in the range from 0 to 0.17) results in the increase of specific capacitance up to a maximum for about 10 at% Ni. The deposition scan rate affects the capacitive behaviour of mixed oxide electrodes through its effects on layer morphology and surface structure. In particular, thin film electrodes at about 10 at% Ni show a maximum in the specific capacitance for deposition scan rate of 600 mV s −1, which is shown to be related to the attendant modifications in surface morphology and topography. After annealing at 200 °C, 6 h, partial crystallization of the amorphous structure of the as-grown mixed oxide takes place with formation of dispersed nanocrystalline domains. The annealed electrode at 10 at% Ni, with mass loading of 0.30 mg cm −2, show the highest specific capacitance (250 F g −1, at 0.1 A g −1 ), and specific energy and power as high as 34.5 Wh kg −1 (at 50 W kg −1 ), and 4.3 kW kg −1 (at 15.7 Wh kg −1 ). Mixed oxide of the same composition and mass loading reveal a 122% capacitance retention after 10, 000 cycles in 1 M Na2 SO4 at 20 A g −1 .